Nerses Ashtaraketsi – Mikhail Vorontsov: New Documents about Friendship : - Hovhannisyan , Haykaz; Bayramyan, Karen (History and Culture, 2022)
In Armenian historiography, there are not so many references to the friendly relations of the Catholicos of all Armenians, Nerses Ashtaraketsi with the governor of the Caucasus, Mikhail Vorontsov. It is an obvious fact that these relations, in addition to personal ones, had a pronounced pro-Armenian orientation. Moreover, the preserved documents in the archive of the famous historian and specialist in Caucasian Studies Alexander Yeritsyan, which are kept in the Matenadaran named after Mesrop Mashtots, give us the opportunity to reveal and analyze many episodes of this friendship, which undoubtedly has historical and historiographical significance. On the other side, the presented documents describe Nerses Ashtaraketsi as a statesman, his intention to use his personal ties to serve the interests of the Armenian nation.
Keywords: Nerses Ashtaraketsi; Catholicos of All Armenians; Mikhail Vorontsov; governor of the Caucasus; Matenadaran; Al. Yeritsyan; correspondence; Russian politics; pro-Armenian position; analysis